Budaya Hukum Praktik Pengangkatan Anak Tanpa Penetapan Pengadilan (Studi Kasus Masyarakat Kecamatan Bukit Bestari Kota Tanjungpinang) - Hidayatullah, Rizki Pradana (Universitas Islam Sumatera Utara, 2022)
Bukit Bestari Subdistrict, Tanjungpinang City, Indonesia, has a strong legal culture for adopting a child without a court order. Consequently, this study aims to better comprehend how legal obstacles affect the adoption process. This study utilizes qualitative research in the form of case studies. Sociology of law was applied to investigate the issue. This study's data was collected through documentation reviews and interviews. According to the findings of this study, people in the Bukit Bestari subdistrict who adopt children without a court order have a positive perspective of the adoption process. However, adopted parents' positive opinions do not always influence adoption court decisions. Suppose a child is adopted without a court order. In that case, there are no legal ties between the adoptive parents and the adopted child because there is no evidence that the adoption was conducted in compliance with the legislation in effect. Therefore, the government's efforts to maintain adoption rights to be registered include the development of laws and implementing regulations and the supervision of their implementation. Keywords: Legal Culture, Child Adoption, Court Decision.